Construction of Integrated Technology for Physical and Mental Health in Conflict-Affected Middle Eastern Regions : A Confirmatory Factor Analysis of the Dimensions of Digital Innovation, Infrastructure Readiness, User Competency, and Sustainability - Mawar, Luthfiah; Rahmadi, M. Agung; Sabila, Sal; Muzhaffirah, Adzra; Rengganis, Mutiara; Nasution, Helsa; Sihombing, Nurzahara; Umaira, Aisyah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
This study offers a comprehensive analysis of the integrated technology construct connecting physical and mental health services in conflict-affected Middle Eastern regions by employing confirmatory factor analysis within a Structural Equation Modelling approach. The research is based on 1,124 documents on digital health technology implementation published between 2017 and 2024 across fourteen countries. The measurement model demonstrates strong goodness-of-fit, evidenced by chi-square/df = 1.847, CFI = 0.971, TLI = 0.965, RMSEA = 0.041, and SRMR = 0.034, thereby confirming the structural soundness of the proposed framework. The analysis identifies four core dimensions—Digital Innovation (lambda = 0.893, CR = 13.672), Infrastructure Readiness (lambda = 0.847, CR = 12.184), User Competency (lambda = 0.819, CR = 11.453), and Sustainability (lambda = 0.865, CR = 12.738)—all significant at p < 0.001. Reliability indices are robust, with Cronbach's Alpha between 0.876 and 0.934, Composite Reliability ranging from 0.891 to 0.947, and Average Variance Extracted between 0.661 and 0.798, indicating strong internal consistency. The findings expand earlier digital health frameworks proposed by Mechael (2009) and Labrique et al. (2013) by emphasizing sustainability as a key component in conflict settings marked by limited resources. In contrast to Aranda-Jan et al. (2014), which addresses general technology adoption, this study underscores specific challenges in integrating both mental and physical health services in humanitarian contexts, thereby responding to the gap highlighted by Naslund et al. (2017) regarding fragmented digital mental health initiatives in crisis environments.